Study on pretrreatment of gaharu oil extraction process - Nor Ilia Anisa, Aris (2008)
Gaharu, the names for the resinous, fragrant and highly valuable heartwood produced by Aquilaria Malaccensis. Gaharu is classified as one of the most valuable forest products traded internationally. Gaharu oil is widely use in religious ceremony, meditation, incense and perfume. Currently, local entrepreneur has adopted hydro distillation technique to complete the extraction process because the advantages of the hydro distillation are less steam usage, the cheapest and simplest process and this is the best method for the powder. However, the percentage of yield is very low and longer time required extracting gaharu oil. To overcome this problem, a study on pretreatment methods will be performed to increase the effectiveness of gaharu oil extracted using hydrodistillation. There were three pretreatment methods studied which are soaking, ultrasonic and ultrasonic with enzymatic. From three of pretreatment methods, hydro distillation process with the assistant of ultrasonic with enzymatic pretreatment contribute the highest efficiency and capacity of gaharu oil extraction which gave 0.12% percentage yield of gaharu oil. However, the further method of pretreatment the gaharu oil in this study was ultrasonic because the increasing percentage yields of ultrasonic was 0.023% compared to the increasing of ultrasonic with enzymatic only 0.009% while the lowest was soaking 0.016%. The percentage of yield with the ultrasonic pretreatment was increased when the duration was increased. The percentage of yield was proportional with time.9 hours of pretreatment time showed the highest percentage of yield rather than other durations (1, 3 and 6 hours). As the conclusion, the ultrasonic pretreatment method is very crucial to improve the extraction process of gaharu essential oil.